Porto-sinusoidal vascular disease: a new definition of an old clinical entity - Barisic-Jaman, Mislav; Milosevic, Marko; Pastrovic, Frane; Skrtic, Anita; Grgurevic, Ivica (Clinical and Experimental Hepatology, 2023)
Porto-sinusoidal vascular disease (PSVD) is defined as a vascular liver disease characterized by the absence of cirrhosis and the presence of characteristic histological features, with or without the presence of portal hypertension (PH). Half of the patients with PSVD also have associated disease that may contribute to the development of PSVD. Patients usually remain asymptomatic until complications of PH arise. Variceal bleeding and portal vein thrombosis are major complications associated with PSVD. The treatment is focused on managing complications of PH, mainly through primary prophylaxis of variceal bleeding and treatment of portal vein thrombosis. Currently, there is insufficient evidence to support the use of anticoagulants for thrombosis prevention in these patients. Despite the increase of recognition of PSVD, further research is needed to enable early disease diagnosis, establish optimal screening methods, and develop strategies to slow down disease progression.